Patient participation in the intensive care unit. (October 2017) - Schandl, Anna; Falk, Ann-Charlotte; Frank, Catharina
Summary: Objective: Patient participation in healthcare is important for optimizing treatment outcomes and for ensuring satisfaction with care. The purpose of the study wasto explore critical care nurses' perceptions of patient participation for critically ill patients. Design and settings: Qualitative data were collected in four separate focus group interviews with 17 nurses from two hospitals. The interviews were analyzed using qualitative content analysis. Findings: Initially, the nurses stated that patient participation in the intensive care unit (ICU) was dependent on the patient's health condition and consciousness. However, during the interviews three descriptive categories emerged from their experience, that is: passive patient participation, one-way communication and nurse/patient interaction. Conclusion: In the ICU, the possibilities for patient participation in nursing care are not only dependent on the patient's health condition but also on the nurse's ability to include patients in various care actions despite physical and/or mental limitations. When the patient is not able to participate, nurses strive to achieve participation through relatives' knowledge and/or other external sources of information.